Model Pembelajaran Kooperatif STAD untuk Meningkatkan Hasil Belajar Materi Dinamika Penduduk di SMP Pangudi Luhur Bintang Laut Surakarta - Stephanus Darminto (Universitas Sebelas Maret, 2019)
This type of research is classroom action research. The purpose of this study was to improve Social Studies learning outcomes in the material of Population Dynamics of Grade VIII D students. The research subject was 39 students Class VIII D of Pangudi Luhur Bintang Laut Surakarta Junior High School. Data collection techniques and tools from learning outcomes use pre-test and post-test learning outcomes. Data analysis uses descriptive qualitative and reflective techniques. The conclusion of this study is the classical completeness of class VIII D students in semester 1 of social studies subjects is 50% can be overcome by applying the type of cooperative learning methods. This research was conducted in two cycles for students of class VIII D semester 1 of Pangudi Luhur Bintang Laut Surakarta Junior High School. Each cycle consists of four components of action research, namely planning, action, observation and reflection. The results also showed an increase in learning outcomes, namely the first cycle with the acquisition of an average grade of 85.85 with 75% classical completeness and the second cycle with an average acquisition of 90.82 with 95% classical completeness. The results obtained indicate that the application of the STAD type cooperative learning model can improve the learning outcomes of students of class VIII D of Pangudi Luhur Bintang Laut Surakarta Junior High School